2011
DOI: 10.3855/jidc.1781
|View full text |Cite
|
Sign up to set email alerts
|

Is short course of antimicrobial therapy for asymptomatic bacteriuria before urologic surgical procedures sufficient?

Abstract: Introduction: Duration of treatment of asymptomatic bacteriuria for patients undergoing urologic surgical procedures is undetermined. We compared the efficacy of long-versus short-course antimicrobial treatment in patients with asymptomatic bacteriuria undergoing urologic surgical procedures. Methodology: Patients were divided into two groups according to duration of antimicrobial treatment. Group A patients received a single dose of an appropriate antibiotic, determined by antimicrobial sensitivity testing, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…The literature search retrieved 14 investigations, with nine fulfilling the inclusion criteria. Five studies analysed antibiotic prophylaxis for transrectal prostate biopsy [10] , [11] , [12] , [13] , [14] , only one study evaluated antibiotic prophylaxis for urological procedures at a general level [15] , and the remaining studies analysed antibiotic therapy for cystoscopy, transurethral prostatic resection and urethral lithotripsy [16] . The studies were published between 1998 and 2013, and were carried out in Chile, Colombia, Taiwan, India, France, Turkey, and China.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature search retrieved 14 investigations, with nine fulfilling the inclusion criteria. Five studies analysed antibiotic prophylaxis for transrectal prostate biopsy [10] , [11] , [12] , [13] , [14] , only one study evaluated antibiotic prophylaxis for urological procedures at a general level [15] , and the remaining studies analysed antibiotic therapy for cystoscopy, transurethral prostatic resection and urethral lithotripsy [16] . The studies were published between 1998 and 2013, and were carried out in Chile, Colombia, Taiwan, India, France, Turkey, and China.…”
Section: Resultsmentioning
confidence: 99%
“…Only the study by Sayin Kutlu et al [15] conducted in Turkey between 2005 and 2008 in 59 patients scheduled for a urological procedure assessed the duration of antibiotic prophylaxis in patients with AB, indicating that there were no significant differences between single-dose therapy (30–60 min before the procedure) with an antibiotic treatment lasting 3–15 days until the urine was sterile before surgery. That study also found significant differences in the reduction of hospital stay and costs of antimicrobials in the single-dose group ( P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study showed that a single dose or two doses of antimicrobial therapy was effective in preventing severe infectious complications such as upper UTI and septicemia following urological procedures in patients with pre-procedure ASB. We had previously come to this conclusion in a small prospective study including 31 procedures [10]. That study showed that shortcourse treatment (one or two doses) of ASB resulted in a significantly shorter length of stay and cost of antimicrobial therapy, while long term treatment was associated with subsequent isolation of a greater number of resistant microorganisms [10].…”
Section: Discussionmentioning
confidence: 99%
“…Although short-course treatment may not eradicate the microorganism from the urinary system, it can prevent bacteremia and sepsis. In our previous study, a single dose of antimicrobial was given to 31 patients 30 to 60 minutes before the surgical procedure and a second dose if a catheter was placed postoperatively, and none of the patients had no severe infectious complications [10]. We reviewed the effectiveness of single or two-dose antimicrobial treatment, and post-procedure infectious complications in a large group of patients in the current study.…”
Section: Introductionmentioning
confidence: 99%